Experimental validation of a topological derivative-based crack growth control method using digital image correlation. Issue 1 (29th September 2021) - Barros, Guilherme; Filho, João; Nunes, Luiz; Xavier, Marcel
Abstract : Purpose: The purpose of this paper is to experimentally validate the crack growth control based on the topological derivative of the famous Rice's integral. Design/methodology/approach: Single edge notch tensile specimens with two configurations were tested. Displacement fields near notch were experimentally obtained using the digital image correlation method. These displacements were used to verify the minimization of the associated shape functional, which is defined in terms of the Rice's integral, when a set of controls (holes) positioned according to the topological derivative information, is inserted. Based on the Griffth's energy criterion, this minimization represents an improvement in the fracture toughness of cracked bodies. Findings: The experimental tests confirmed that a decrease around 27% in the value of the associated shape functional can be obtained following this approach. Therefore, the results allow us to conclude that the predictive methodology for crack growth control based on the topological derivative is feasible. Originality/value: This is the first work concerning experimental validation of crack growth control based on the topological derivative method.